Phenolic Compounds - Natural Sources, Importance and Applications 2017
DOI: 10.5772/66927
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds in Water: Sources, Reactivity, Toxicity and Treatment Methods

Abstract: Phenolic compounds exist in water bodies due to the discharge of polluted wastewater from industrial, agricultural and domestic activities into water bodies. They also occur as a result of natural phenomena. These compounds are known to be toxic and inflict both severe and long-lasting effects on both humans and animals. They act as carcinogens and cause damage to the red blood cells and the liver, even at low concentrations. Interaction of these compounds with microorganisms, inorganic and other organic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
175
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(208 citation statements)
references
References 77 publications
2
175
0
1
Order By: Relevance
“…48 It can severely destroy the microbial structure causing the release of intracellular components, which are then oxidized. 65 These disadvantages commonly suggest the use of lower concentration of disinfectants to produces less toxic effects; hence optimization of disinfectants concentration for hospital setup is essential and need of current time. In NaClO 2 treatment, hypochlorite ion is a crucial factor determining the cleaning efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…48 It can severely destroy the microbial structure causing the release of intracellular components, which are then oxidized. 65 These disadvantages commonly suggest the use of lower concentration of disinfectants to produces less toxic effects; hence optimization of disinfectants concentration for hospital setup is essential and need of current time. In NaClO 2 treatment, hypochlorite ion is a crucial factor determining the cleaning efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira (2012) reported that the inhibition of seed germination percentage was associated with high TDS and Cr ion in wastewater causing the osmotic stress and toxicity in plants (Kasoobi, 2017). Phenolics content in wastewater alters the homeostatic of plants through the over production of reactive oxygen species as reported earlier (William et al, 2017;Lyu et al, 2018).…”
Section: Phytotoxicity Of Tannery Wastewatermentioning
confidence: 80%
“…Phenol compounds are chemicals listed as pollutants with a priority interest by the United States Environmental Protection Agency (USEPA) and European Union (EU) (Anku et al, 2017). Consequently, high phenol concentrations in the aquatic environment should be a concern because of the toxicity and long-term accumulations.…”
Section: Phenolmentioning
confidence: 99%